FEE-BASED SERVICES AS A CATALYST FOR ENHANCED SERVICE DELIVERY IN NIGERIAN UNIVERSITY LIBRARIES - Idubor, Imade; Stella, Ejitagha (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Humaniora Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The study examined fee-based services as a catalyst for enhanced service delivery in Nigerian university libraries through the lens of the Resource-Based View (RBV) theory. The survey design was descriptive, and the study population comprises all the librarians working in university libraries in Nigeria. The census sampling technique was adopted, and an online questionnaire was used to collect data. The online questionnaire was administered to the librarians, and 202 completed it, and with that, the analysis was made. Findings revealed that Nigerian university libraries offer a range of fee-based services, including binding, photocopying, and user registration, while other more specific services, such as data analysis and laptop lending, are less offered. Fee-based services have a positive influence on the quality and the efficiency of the delivery of library service, and the number of fee-based services provided will influence the perceived quality of library service delivery in Nigerian university libraries to a very high extent. However, obstacles, such as funding constraints and logistical challenges, price policy uncertainty, accountability and remittance, poor planning, low user awareness, and lack of staff training, impact the effective execution of fee-based services in Nigerian university libraries. The hypothesis test revealed a very strong and significant relationship between the number of fee-based services provided and the quality of library service delivery in Nigerian university libraries. The authors recommended that university libraries in Nigeria should diversify into providing specialized feebased services, such as data analysis and lending of laptops, with investment in staff training and the provision of ICT infrastructure. Transparency and user confidence will increase as a result of clear policies and pricing structures.